The Intervention of Foot Care Education in the Prevention of Diabetic Foot Ulcers: A Literature Review - Saltar, Laode; Sahar, Junaiti (Universitas Muhammadiyah Surakarta, 2020)
Purpose: The aim of this literature review was to get an overview of the methods and strategic interventions of foot care education in the prevention of diabetic foot ulcers (DFU).Methodology: The literature search focused on ‘foot care education in the prevention of diabetic foot ulcers’. A number of databases such as Springer Link, EBSCOhost (Academic Search Complete), ProQuest, and Science Direct were searched for relevant articles. Literature search using keywords such as “type 2 dm”, “education”, “prevention” and “diabetic foot ulcer.” All types of articles were included for the study, such as systematic reviews, randomized controlled trial, quasi-experiment, and literature review with the range 2010-2020. Only articles in English are included in this review. Results: Based on keywords, it was identified nine articles that focus on intervention of foot care education to prevent diabetic foot ulcers. The literature review summarized the discussion about the methods of providing education, duration and follow up, the teams involved, and the effectiveness of educational interventions. The objectives of providing educational interventions are individuals, families and groups. The method of providing education was carried out face-to-face in clinics, hospitals, and at home, by phone and through android applications such as youtube. The intervention of foot care education effectively improves foot care knowledge, self-efficacy of foot care, foot care behavior, glycemic control, reduce skin and nail problems, improve diabetic foot, decrease DFU incidence, and improve the quality of life.Applications/Originality/Value: This review can be a reference for nurses and other health professionals in choosing the best methods and strategies for foot care education tailored to existing resources.